133k views
4 votes
Multiply the polynomials (x+2)(2x^2+9x+8)

User JXPheonix
by
5.5k points

2 Answers

4 votes
When you combine like terms you would get
2x^3+13x^2+26x+16
Have a great day!!!
User Bsmoo
by
6.0k points
7 votes

Answer with explanation:

We have to multiply a binomial with Trinomial.


\rightarrow(x+2)(2x^2+9 x +8)\\\\=x * (2 x^2+9x+8)+2* (2 x^2+9x+8)\\\\=2x^3+9x^2+8 x+4 x^2+18 x+16\\\\ \text{adding like terms}\\\\=2 x^3+13 x^2+26 x+16\\\\ \text{used distributive property of multiplication with respect to addition and law of indices}}\\\\x^a* x^b=x^(a+b)\\\\a * (b+c)=a * b+a * c

User Heyitsvajid
by
6.1k points